RENAL LOWER POLE RATIO AS A PREDICTOR OF LOWER POLE STONE CLEARANCE AFTER EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY (Iraqi Journal of Medical Sciences, 2016)
Background:The Lower pole anatomy (apart from other factors: stone size, shock wave energy) is an important determinant of success after extracorporeal shockwave lithotripsy.Objectives:In this study, we aimed to determine if there is a significant relationship between lower pole ratio (infundibular length: infundibular width) on preoperative excretory urograms and stone fragment clearances after shockwave lithotripsy.Methods: A total of 60 patients with isolated lower pole stones were prospectively included in the study. Anatomical factors, such as infundibular length and width were measured and the lower pole ratio was calculated on pretreatment excretory urogram. Stone fragment clearance was assessed on periodic follow up visits (1-8weeks) with a plain abdominal X-ray for kidney, ureter and bladder.Results:The overall eight-week stone-free rate was 56.66%. Mean stone size ± SD was 11.383 ± 5 mm, mean infundibular length was 11.95 ± 6.52 mm, mean infundibular width was 4.25 ± 1.66 mm and mean lower pole ratio was 3.2 ± 2.4. Stone free status after shockwave lithotripsy was significantly related to infundibular length and width as well as to lower pole ratio. Infundibular length less than 25 mm, width greater than 4 mm and lower pole ratio less than 3.5 were noted to have an improved eight week stone-free rate.Conclusion:Lower pole anatomy is an important predetermining factor for lower pole stone clearance after shockwave lithotripsy. The present study suggests that a lower pole ratio of less than 3.5, which considers both infundibular length and width, is a promising and easily applicable predictor for stone-free status.Key words:Lower pole ratio, extracorporeal shockwave lithotripsy, stone clearance.
Keywords: Lower pole ratio; extracorporeal shockwave lithotripsy; stone clearance